Synergy of pharmacotherapy and physical activity in the treatment of obesity and cardiovascular prevention in patients with type 2 diabetes - Mędrysa, Karolina; Jankowska, Marlena; Baran, Karolina; Jańczyk, Natalia; Blecharz, Gabriela; Presak, Michał; Bartnik, Katarzyna; Pokrzepa, Jakub Jan; Szwech, Julia; Pograniczny , Mikołaj (Quality in Sport, 2025)
Aim of the study The aim of this paper is to explore the synergistic role of pharmacotherapy and physical activity in the treatment of obesity and the prevention of cardiovascular diseases in patients with type 2 diabetes. Materials and methods This review is based on selected publications from 1999 to 2025, retrieved from PubMed, WHO, and StatPearls using keywords related to type 2 diabetes, pharmacotherapy, and physical activity. Included were guidelines, clinical trials, and meta-analyses focusing on adults with T2DM. In total, 38 sources were analyzed, covering treatments such as metformin, GLP-1 receptor agonists, SGLT2 inhibitors, DPP-4 inhibitors, and lifestyle interventions [1–28]. Results The combination of pharmacotherapy and physical activity in T2DM patients led to better glycemic control, greater weight reduction, and improved cardiovascular outcomes compared to either intervention alone. Conclusion The management of type 2 diabetes (T2DM) and its associated complications, particularly cardiovascular disease (CVD) and obesity, requires a multifaceted approach. Pharmacotherapy and physical activity are two critical components in the treatment and prevention of these conditions. While each of these interventions offers distinct benefits, their combination provides enhanced outcomes that are greater than the sum of their individual effects.